Response inhibition in motor conversion disorder. Issue 5 (2nd April 2013) - Voon, Valerie; Ekanayake, Vindhya; Wiggs, Edythe; Kranick, Sarah; Ameli, Rezvan; Harrison, Neil A.; Hallett, Mark
ABSTRACT Conversion disorders (CDs) are unexplained neurological symptoms presumed to be related to a psychological issue. Studies focusing on conversion paralysis have suggested potential impairments in motor initiation or execution. Here we studied CD patients with aberrant or excessive motor movements and focused on motor response inhibition. We also assessed cognitive measures in multiple domains. We compared 30 CD patients and 30 age‐, sex‐, and education‐matched healthy volunteers on a motor response inhibition task (go/no go), along with verbal motor response inhibition (color‐word interference) and measures of attention, sustained attention, processing speed, language, memory, visuospatial processing, and executive function including planning and verbal fluency. CD patients had greater impairments in commission errors on the go/no go task (P < .001) compared with healthy volunteers, which remained significant after Bonferroni correction for multiple comparisons and after controlling for attention, sustained attention, depression, and anxiety. There were no significant differences in other cognitive measures. We highlight a specific deficit in motor response inhibition that may play a role in impaired inhibition of unwanted movement such as the excessive and aberrant movements seen in motor conversion. Patients with nonepileptic seizures, a different form of conversion disorder, are commonly reported to have lower IQ and multiple cognitive deficits. Our results point toward potential differences between conversion disorder subgroups. © 2013 Movement Disorder Society